2011
DOI: 10.1016/j.jcm.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for adult scoliosis patients receiving chiropractic rehabilitation: a 24-month retrospective analysis

Abstract: This report is among the first to demonstrate sustained radiographic, self-rated, and physiologic benefits after treatment ceased. After completion of a multimodal chiropractic rehabilitation treatment, a retrospective cohort of 28 adult scoliosis patients reported improvements in pain, Cobb angle, and disability immediately following the conclusion of treatment and 24 months later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 13 publications
4
20
0
2
Order By: Relevance
“…Data obtained by us is comparable and better than those described by other authors (21,22) six months after administration of chiropractic rehabilitation and automatic reflex 3D correction in 28 patients aged over 18 years (17-60 years) with a minimum scoliosis of 30° (average 44°±6°) by Cobb. Scoliosis in adults is associated with a lower quality of life (5,23), low results from health questionnaire SF-36 (11,24) and prone to development of chronic pain, more often compared to the general population (13).…”
Section: Discussionsupporting
confidence: 86%
“…Data obtained by us is comparable and better than those described by other authors (21,22) six months after administration of chiropractic rehabilitation and automatic reflex 3D correction in 28 patients aged over 18 years (17-60 years) with a minimum scoliosis of 30° (average 44°±6°) by Cobb. Scoliosis in adults is associated with a lower quality of life (5,23), low results from health questionnaire SF-36 (11,24) and prone to development of chronic pain, more often compared to the general population (13).…”
Section: Discussionsupporting
confidence: 86%
“…The authors demonstrated sustained radiographic, self-rated, and psychological benefits after treatment ceased. 29 Chiropractic treatment was also associated with a reduction in a severe case of adolescent idiopathic scoliosis (46°Cobb angle) in a young female after she had previously received conservative medical treatment that failed to stop curve progression. 30 Currently, nonsurgically treated patients are encouraged to participate in sports and physical activity; and scoliosis is not a contraindication to participation in most sports 31 ; therefore, this could also increase the QoL of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…These external postural weights purposely alter the centers of mass of the head, torso, and pelvis in specific vectors to cause automatic neuromuscular responses to counterbalance the external weight in predictable dimensions. Examples of this postural weighting process have been previously reported in scoliosis treatment .11,12,15 All patients in this study were prescribed their own sets of this weighting system for both in-office treatment as well as home use. Patients performed proprioceptive balancing on a 24-inch vestibular disc while using a cantilever exercise apparatus that increases the leverage of these externally placed postural weights without needing to add extra weight.…”
Section: Methodsmentioning
confidence: 97%